Visualization of finite-time separation in multiphase flow - Heinemann, Moritz; Potyka, Johanna; Schulte, Kathrin; Sadlo, Filip; Ertl, Thomas (IEEE transactions on visualization and computer graphics, 2024)
This article presents a particle-based visualization approach for finite-time analysis of the connectivity of fluid portions in multiphase flow, i.e., the evolution of the droplets in volume of fluid simulations. We address the Lagrangian inconsistency between the interpolated flow field and the interpolated volume of fluid field by a correction approach, and complement that with an uncertainty measure that provides an estimate of the involved inconsistency. We demonstrate the utility and versatility of our approach using different multiphase flow simulations, exemplify its application in physics-based assessment of droplet formation processes, and discuss its limitations and benefits.
Gesehen am 24.07.2025